(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study aims to explore how work-life balance affects job performance. It also looks at how mediating and moderating effect of job satisfaction and family-supportive supervisor behavior influence this relationship in Commercial Banks. Methods: It followed a descriptive and causal-comparative research design and applied various statistical methods for data analysis, such as mean, standard deviation, independent t-test, parametric and non-parametric tests, and correlation analysis. Data collection was executed through the purposive sampling Method, from which 211 responses were obtained from employees of commercial bank. The study used a adopted questionnaire with a seven-point Likert scale. Results: The results showed that work-life balance is the main factor affecting job performance. Additionally, the study also revealed that a supervisor’s supportive behavior toward family matters influences the relationship between job satisfaction and job performance. Moreover, job satisfaction partially mediates the connection between work-life balance and job performance. Conclusion: The study concludes that to enhance job performance, commercial banks should prioritize promoting work-life balance, supportive supervisor behaviors regarding family matters and improve job satisfaction among employees.